Efektivitas Model Pembelajaran Picture and picture terhadap Hasil Belajar IPA Siswa di Sekolah Dasar - Nursida, Naja; Kurniawati, Nining; Kamarudin, Kamarudin; Yulianci, Syahriani; Nurjumiati, Nurjumiati (STKIP Taman Siswa Bima, 2024)
This study aims to evaluate the effectiveness of the Picture and picture learning model in improving science learning outcomes at SDN Inpres Kawae. The methodology employed was a quasi-experimental design with a subject group of 13 fifth-grade students, comprising 1 male and 12 female students. Data were collected using a test instrument to measure learning outcomes before and after the implementation of the Picture and picture learning model. The results indicate a significant improvement in students' learning outcomes. Before the implementation of the model, no students achieved the very high category (scores 76-100) on the pretest. However, after implementation, 7 students (about 45% of the total sample) reached the very high category on the posttest. This demonstrates that the Picture and picture learning model is effective in enhancing the effectiveness of science learning outcomes at SDN Inpres Kawae